Arahan Pengembangan Infrastruktur dalam Mendukung Ketahanan Pangan Di Kecamatan Bataguh, Kabupaten Kapuas - Endro Elmanuah; Eko Budi Santoso (Dinasti Research, 2024)
Bataguh District has great potential for agricultural resources and is the largest rice producing area in Kapuas Regency, based on field conditions, the existing infrastructure is not yet supportive and most of the infrastructure is still not optimal, so efforts are needed to develop infrastructure for the agricultural sector and resilience. food in Bataguh District. This research aims to determine the infrastructure needed to support regional development of the agricultural sector and food security. Starting with the analysis looking for the basic infrastructure needed in the agricultural sector, starting with a descriptive analysis stage to identify the condition of the infrastructure in the field. The next stage involves using the Importance-Performance Analysis method to evaluate the level of importance and performance of the infrastructure. In the final stage, triangulation analysis is used to conclude the results and provide development directions to support the agricultural sector and food security in Bataguh District, Kapuas Regency. Based on the research results, it is known that the priorities for infrastructure groups are: quadrant 1 (Road Network, Agricultural Irrigation, Storage Warehouses and Agricultural Processing Facilities), quadrant 2 (Communication Network and Electricity Network Coverage), quadrant 3 (Clean water network, Availability of Sanitation, Cooperatives , and gas stations) and quadrant 4 (Modes of Transportation, Markets, and Transportation Support Facilities).